6+3x+6x=-3+x+1+7x

Simple and best practice solution for 6+3x+6x=-3+x+1+7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+3x+6x=-3+x+1+7x equation:


Simplifying
6 + 3x + 6x = -3 + x + 1 + 7x

Combine like terms: 3x + 6x = 9x
6 + 9x = -3 + x + 1 + 7x

Reorder the terms:
6 + 9x = -3 + 1 + x + 7x

Combine like terms: -3 + 1 = -2
6 + 9x = -2 + x + 7x

Combine like terms: x + 7x = 8x
6 + 9x = -2 + 8x

Solving
6 + 9x = -2 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
6 + 9x + -8x = -2 + 8x + -8x

Combine like terms: 9x + -8x = 1x
6 + 1x = -2 + 8x + -8x

Combine like terms: 8x + -8x = 0
6 + 1x = -2 + 0
6 + 1x = -2

Add '-6' to each side of the equation.
6 + -6 + 1x = -2 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = -2 + -6
1x = -2 + -6

Combine like terms: -2 + -6 = -8
1x = -8

Divide each side by '1'.
x = -8

Simplifying
x = -8

See similar equations:

| 8-2v-2=3-3v | | 7x-8-3x=24 | | 1+9=9+1 | | z+18=30 | | 10x+5Y=3621 | | 122-6x=21x+23 | | 122-6x=221x+23 | | 10-7x=30-14x | | -65-8x=8x+15 | | x^3-2x^2-3x=0 | | -42-3x=6-9x | | 9x^2+24x=-16 | | 3(2x+4)+8=50 | | ax=bx+c | | 4x^2=-12x+10 | | 10a-5b=12 | | x(4x^2-20x+24)=0 | | 8+3x=23 | | 100y+30=120y+90 | | x-6=x+21 | | x-6=x-21 | | 3(3-4d)=57 | | 3x+14=20-2x | | 9s+5=s+7 | | 2c-1=1-2c | | 15x+10=40 | | 5x-95=2x-5 | | .6y=-.75 | | x^4-27x=0 | | f(3)=x^3+2x^2-x-1 | | 10-7x=61-28x | | -66-10x=7x+19 |

Equations solver categories